Delta Preservation and Handling Diversion Abrasion Coastal Model of The Sudeten Wulan River (Case of Study in Land Arising Coastal Wedung, Demak, Central Java) - Fatchur Roehman, ST. MT (International Conference on Coastal and Delta Areas, 2015)
The research makes the preservation of coastal security models in land development arose as an effort in face the impact of reclamation Marina Beach Semarang in theway making the Sudetan Wulan Beach and security of Semat Beach district of Jepara. The method used is the field survey method using the instrument as a guide in-depth interviews, direct observation, calculation of sediment and documentation. Sources of information from the local public and government. Triangulation techniques implemented in collecting the data. Meanwhile, in reducing data from public aspirations used Focus Group Discussion (FGD) Method. The data analysis was performed by observing the increase of land arises, quantitative and qualitativeapproach. Based on the result of analysis seen that the disaster in the coastal abrasion in Demak and Jepara is getting worse in Babalan Village, Wedung Regency. The effort that people do in face the abration in the area by making sudeten to right side in Babalan Beach. However, previous research results were not optimal in handling abrasion, one side Semat Coastal Jepara was erosion but on the other side in Wedung Beach annually formed delta (soil arising altered form of pond) which is enlarge, due to the results of the sediment carried by the flooding of Wulan Riveraccumulate in estuaries beach and wave scour sediment flows from the direction of change reclamation Marina Beach Semarang.